Caspase-8 as a Regulator of Tumor Cell Motility - Graf, R.P.; Keller, N.; Barbero, S.; Stupack, D. (Current Molecular Medicine, 2014)
The caspases are a family of ubiquitously expressed cysteine proteases best known for their roles in programmed cell death. However, caspases play a number of other roles in vertebrates. In the case of caspase-8, loss of expression is an embryonic lethal phenotype, and caspase-8 plays roles in suppressing cellular necrosis, promoting differentiation and immune signaling, regulating autophagy, and promoting cellular migration. Apoptosis and migration require localization of caspase-8 in the periphery of the cells, where caspase-8 acts as part of distinct biosensory complexes that either promote migration in appropriate cellular microenvironments, or cell death in inappropriate settings. In the cellular periphery, caspase-8 interacts with components of the focal adhesion complex in a tyrosine-kinase dependent manner, promoting both cell migration in vitro and metastasis in vivo. Mechanistically, caspase-8 interacts with components of both focal adhesions and early endosomes, enhancing focal adhesion turnover and promoting rapid integrin recycling to the cell surface. Clinically, this suggests that the expression of caspase-8 may not always be a positive prognostic sign, and that the role of caspase-8 in cancer progression is likely context-dependent.
Keywords: nonapoptotic